Altered PLD3 exonuclease activity impacts on lysosomal and mitochondrial homeostasis. (20th December 2022) - Van Acker, Zoë P.; Bretou, Marine; Sannerud, Ragna; Damme, Markus; Annaert, Wim
Abstract: Background: Phospholipase D3 (PLD3) is a single‐pass type II membrane protein that is majorly localized to late endosomes/lysosomes (LE/Lys) where it functions as a 5'‐3' exonuclease that degrades ssDNA. Whereas PLD3 has been identified as risk factor for late‐onset Alzheimer's disease (LOAD), knockout studies have resulted in conflicting data regarding its impact on the amyloid precursor protein metabolism. Moreover, the substrates for PLD3 in LE/Lys remain unexplored Method: CRISPR/Cas9 gene editing was used to generate PLD3 knockout (KO) SH‐SY5Y cells that were subsequently stably rescued with wild‐type PLD3 and coding‐variants (M6R & V232M). All cell lines were evaluated for morphological and functional alterations of the LE/Lys compartment, including lipid profiling and analysis of the nucleotide content of LE/Lys magnetically isolated from the different cell lines. We optimized a PLD3 activity assay and analyzed the LE/Lys nucleotide content as a means to identify PLD3 substrates. Result: We report that a PLD3 KO and LOAD‐associated risk variants lead to a significant lysosomal pathology, comprising an increase in the size of LE/Lys, more LAMP1 immunoreactivity, a reduced catabolic activity, an increased propensity for leakage and a marked increase in cholesterol content and in storage lipids. At the ultrastructural level, this is accompanied with the appearance of multilamellar bodies, sometimes including mitochondrial remnants. This is suggestive for a defective mitophagy, which we confirm on the light microscopy level using mKeima assays. Furthermore, we provide support for a role of PLD3 in the homeostatic degradation of mtDNA. We argue that when PLD3's role is compromised, this leads to a build‐up of the lysosomal nucleotide content, impacting on the normal functioning of LE/Lys. We are currently analysing alterations in downstream cellular signaling pathways, including the TLR9 cascade. Conclusion: Collectively, our findings subscribe a key role for PLD3 exonuclease activity in lysosomal homeostasis. Its dysfunction, as occurs in LOAD, leads to the co‐occurrence of lysosomal and mitochondrial defects.